A novel hyperbranched polyurethane/nTiO2 waterborne sizing agent for improving UV-resistance and interfacial properties of SCF/PA6 composites. (February 2021) - Fang, Lanqing; Qiu, Tingtian; Yang, Quan; Kong, Lingqiang; Yan, Fei; Zhang, Mengjie; Liu, Yu; Liu, Liu; Ao, Yuhui
Abstract: In this study, a novel UV-resistant hyperbranched polyurethane (HBPU) was designed and processed into a series of waterborne sizing agents for short carbon fiber (SCF). The content of functional groups on the SCF surface was subsequently increased, leading to improvement of the interfacial adhesion of SCF/polyamide6 (PA6) composites. According to the mechanical property results, SCF/PA6 composites with 0.5 wt% sizing agent showed the best reinforcing effect, with the tensile and bending strength increased by 41.4% and 26.4%, respectively. The mechanisms for the enhancement of the interfacial adhesion by sizing agent were investigated. Noteworthy, the mechanical properties of the sizing SCF/PA6 composites remained about 99% after a week of uninterrupted UV aging treatment, indicating the excellent UV resistance of the nTiO2 grafted HBPU sizing agent. Highlights: The bio-based hyperbranched polyurethane sizing agents for CF/PA6 were prepared. The nTiO2 was grafted onto HBPU to improve UV-resistance of sizing agent. The tensile and bending strength of composites were improved by 41.4% and 26.4%. The mechanical properties of composites were retained over 98% after UV aging.